Human Detection and Classification using Passive forward Scattering Radar - Hafizah Abdul Aziz, Noor; Ain Ali, Nurul’; ., . (International Journal of Engineering and Technology, 2018)
Passive forward scattering radar is a system that can detect any present object that is passing through between the transmitter and receiver. The technique used for detection of human is called forward scattering technique. It is used to detect human who passes within the range of forward scatter region. Moreover, passive radar system doesn’t have its own transmitter but it can receive the power signal from any commercial transmitters. For this research work, commercial transmitters that transmit frequency of Long-Term Evolution (LTE) which is 1.8 GHz were used. When a human passes through between the transmitter and receiver, a wave called the Doppler signal is produced in the forward scatter region, and it is then captured by the passive radar receiver. For data acquisition, 3 individuals of different height were involved, which is Person 1 (1.57m), Person 2 (1.56m) and Person 3 (1.47m), and the location of the experimental work was constructed in the real environment at the seaside of Morib, Malaysia. The reason the seaside was chosen was based on past cases of intruders crossing the border of Malaysia through the seaside at Lahad Datu, Sabah. All of the data was collected and analyzed using Matlab software. From the experiment results, it was shown that the passive forward scattering radar system successfully detected and classified the human presence while walking and running, where running was more easily classified because of the increasing speed compared to walking.